The Use of Autologous Cell Therapy in Diabetic Patients with Chronic Limb-Threatening Ischemia - Sojakova, Dominika; Husakova, Jitka; Fejfarova, Vladimira; Němcová, Andrea; Jarosikova, Radka; Kopp, Simon; Lovasova, Veronika; Jude, Edward B; Dubsky, Michal (International journal of molecular sciences, 2024)
Autologous cell therapy (ACT) is primarily used in diabetic patients with chronic limb-threatening ischemia (CLTI) who are not candidates for standard revascularization. According to current research, this therapy has been shown in some studies to be effective in improving ischemia parameters, decreasing the major amputation rate, and in foot ulcer healing. This review critically evaluates the efficacy of ACT in patients with no-option CLTI, discusses the use of mononuclear and mesenchymal stem cells, and compares the route of delivery of ACT. In addition to ACT, we also describe the use of new revascularization strategies, e.g., nanodiscs, microbeads, and epigenetics, that could enhance the therapeutic effect. The main aim is to summarize new findings on subcellular and molecular levels with the clinical aspects of ACT.
Keywords: Chronic Limb-Threatening Ischemia; Ischemia; Mesenchymal Stem Cell Transplantation; Diabetes Mellitus; Cell- and Tissue-Based Therapy; buněčná a tkáňová terapie; autologní transplantace; transplantace mezenchymálních kmenových buněk; Humans; Transplantation, Autologous; lidé; diabetes mellitus; chronická kritická ischemie končetin; ischemie